A second look at thorstein veblen the aesthetics of thorstein veblen revisited - Tilman, R.; Griffin, R. (Cultural Dynamics, 1998)
The aesthetics of Thorstein Veblen (1857-1929) have been evaluated by aestheticians and social scientists of various ideological persuasions. Because of Veblen's stature as an American critical theorist and the debate which has ensued over the nature of his aesthetics, further efforts to both clarify and extrapolate from them are self-justificatory. The focus here is on (1) Veblen's view of aesthetic experience, (2) the nature of the non-invidiously beautiful in his aesthetics, (3) his distinction between pure and applied art forms and its importance to the common person and (4) the social basis and artistic consequences of the non-invidious as exemplified in the painting of the American artist Winslow Homer (1836-1910). Problematic areas in Veblen's social theory and aesthetics are addressed and a non-invidious aesthetic of countervailence articulated using Homer's work. Copyright © 1998 SAGE Publications.
Keywords: Aesthetic countervailence economics non-invidious aesthetics; dept.com

What veblen owed to peirce - the social theory of logic - Griffin, R (Journal of Economic Issues, 1998)
Keywords: dept.com